2008
DOI: 10.1523/jneurosci.1447-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Myeloid Cells for Axon Regeneration

Abstract: The role of CD11b+ myeloid cells in axonal regeneration was assessed using axonal injury models and CD11b-TK(mt-30) mice expressing a mutated HSV-1 thymidine kinase (TK) gene regulated by the myeloid-specific CD11b promoter. Continuous delivery of ganciclovir at a sciatic nerve lesion site greatly decreased the number of granulocytes/inflammatory monocytes and macrophages in the distal stump of CD11b-TK(mt-30) mice. Axonal regeneration and locomotor function recovery were severely compromised in ganciclovir-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
194
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(197 citation statements)
references
References 61 publications
3
194
0
Order By: Relevance
“…both models of inflammatory pain, we treated CD11b-TK transgenic mice with the nucleoside analog ganciclovir (GCV). The myeloid-specific gene CD11b in these mice drives a mutant form of the suicidal Herpes simplex virus 1 thymidine kinase gene (HSV1-TK mt-30 ), and HSV1-TK mt-30 phosphorylates GCV to inhibit DNA synthesis (30,31), ablating all proliferating transgene positive cells. We found that this treatment resulted in a specific loss of proliferating CD11b + Ly6G − myeloid cells, but not of CD11b + Ly6G + neutrophils (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…both models of inflammatory pain, we treated CD11b-TK transgenic mice with the nucleoside analog ganciclovir (GCV). The myeloid-specific gene CD11b in these mice drives a mutant form of the suicidal Herpes simplex virus 1 thymidine kinase gene (HSV1-TK mt-30 ), and HSV1-TK mt-30 phosphorylates GCV to inhibit DNA synthesis (30,31), ablating all proliferating transgene positive cells. We found that this treatment resulted in a specific loss of proliferating CD11b + Ly6G − myeloid cells, but not of CD11b + Ly6G + neutrophils (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clearance of myelin debris is an important part of the regenerative response, as myelin contains axon outgrowth inhibitors and delayed myelin clearance is associated with impaired axon regeneration [87]. There is evidence that NRG1 may act as an early signal between damaged axons and SCs, promoting myelin breakdown [80].…”
Section: Endogenous Nrg1 May Have a Role In The Early Events Of Wallementioning
confidence: 99%
“…At presymptomatic time points (i.e., weeks 9-12), focal activation occurs for PNS macrophages and spinal cord microglia. Following clinical onset (i.e., weeks [12][13][14][15][16][17][18][19], activation of innate immunity becomes widespread in both tissues as indicated by FACS and histological analysis.…”
Section: Macrophage Activation Occurs Throughout the Peripheral Nervousmentioning
confidence: 99%
“…Mutant SOD1 also induces defects in peripheral axon transport, which may be a primary determinant of motor neuron death (13). In acute models of PNS injury, myeloid cells have been shown to mediate the processes of myelin clearance and subsequent axon regeneration (14). Whether and how the immune system participates in motor axon loss during ALS disease progression remains unexplored.…”
mentioning
confidence: 99%